2022
DOI: 10.1177/20101058221106283
|View full text |Cite
|
Sign up to set email alerts
|

Fat-to-lean mass ratio as a new anthropometric indicator in predicting metabolic syndrome among Malay adolescents in Terengganu, Malaysia

Abstract: Background Metabolic syndrome (MetS) is defined as a cluster of risk factors for predicting type 2 diabetes mellitus and cardiovascular disease. Objectives This cross-sectional study aimed to develop a cut-off value for fat versus lean mass ratio (FLMR) in predicting MetS and to investigate the association between this indicator with MetS and its components. Methods Subjects comprised 238 Malay adolescents (79% female) aged 18–19 years old. Anthropometric assessment comprised weight, height and waist circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, these indicators have some shortcomings as they only focus on the effect of fat and non-fat component independently and do not consider the antagonistic effects of fat mass and lean mass on the health of participants. Relevant studies have recognized the role of the fat-to-lean mass ratio in predicting health conditions in adults, such as the prediction of metabolic syndrome in adults ( 49 ). In a recent epidemiological study, Dai et al ( 14 ) found that for each 1 standard deviation increase in the fat-to-lean mass ratio, the odds ratio for the risk of developing the nonalcoholic fatty liver disease was 1.55 vs. 1.33 in non-obese and obese males, and 1.42 vs. 1.29 in non-obese and obese females, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these indicators have some shortcomings as they only focus on the effect of fat and non-fat component independently and do not consider the antagonistic effects of fat mass and lean mass on the health of participants. Relevant studies have recognized the role of the fat-to-lean mass ratio in predicting health conditions in adults, such as the prediction of metabolic syndrome in adults ( 49 ). In a recent epidemiological study, Dai et al ( 14 ) found that for each 1 standard deviation increase in the fat-to-lean mass ratio, the odds ratio for the risk of developing the nonalcoholic fatty liver disease was 1.55 vs. 1.33 in non-obese and obese males, and 1.42 vs. 1.29 in non-obese and obese females, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Low physical fitness in young people should be carefully monitored as it could affect their maturation and subsequent physical development ( 52 ). In particular, low cardiorespiratory endurance increases the risk of developing metabolic syndrome ( 49 ), cardiovascular diseases ( 53 ), and type 2 diabetes ( 54 ). Poor cardiovascular endurance also increases all-cause mortality rates even in healthy individuals and patients ( 55 ).…”
Section: Discussionmentioning
confidence: 99%